1992
DOI: 10.1002/jmv.1890370209
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 2′‐fluorinated arabinosyl‐pyrimidine nucleosides on duck hepatitis B virus DNA level in serum and liver of chronically infected ducks

Abstract: The 2'-fluorinated arabinosyl-pyrimidine nucleosides, 1-(2'-deoxy-2'-fluoro-beta-D-arabinofuranosyl)-5-iodocytosine (FIAC) and 1-(2'-deoxy-2'-fluoro-beta-D-arabinofuranosyl)-5-methyluracil (FMAU), are new antiviral compounds with in vitro inhibitory activity against the DNA polymerase of hepadnaviruses. Those compounds also induced permanent inhibition of viral replication in woodchucks chronically infected by woodchuck hepatitis virus. The effects of these antiviral compounds were assessed in ducks chronicall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
22
0

Year Published

1994
1994
2003
2003

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 19 publications
0
22
0
Order By: Relevance
“…1, compound 2), is one of a series of 2'-fluoro-substituted arabinosyl pyrimidine nucleosides that have demonstrated potent antiviral activities against a number of clinically important viruses, including hepatitis B virus (HBV) (7,11,28,47). Analogs of FIAU have been shown to inhibit viral replication in the woodchuck and duck models of HBV infection (18,19). Although the mechanism of the anti-HBV activity is not well understood, evidence suggests that the triphosphate analog of FIAU is a potent inhibitor of HBV DNA polymerase activity (17,23,43).…”
mentioning
confidence: 99%
“…1, compound 2), is one of a series of 2'-fluoro-substituted arabinosyl pyrimidine nucleosides that have demonstrated potent antiviral activities against a number of clinically important viruses, including hepatitis B virus (HBV) (7,11,28,47). Analogs of FIAU have been shown to inhibit viral replication in the woodchuck and duck models of HBV infection (18,19). Although the mechanism of the anti-HBV activity is not well understood, evidence suggests that the triphosphate analog of FIAU is a potent inhibitor of HBV DNA polymerase activity (17,23,43).…”
mentioning
confidence: 99%
“…A short half-life for viral eee DNA means that longterm therapy with an inhibitor of DHBV DNA replication would be expected to eventually eliminate this molecule from infected hepatocytes. Studies to date in vivo using viral DNA synthesis inhibitors have proven to be ineffective in curing infected hepatocytes (Wang et al, 1991;Fourel et al, 1992;Fourel et al, 1994;Mason et al, 1994). In one clinical study it has even been shown that longer term treatment of chronically infected patients with a-interferon caused an increase in the amount of intrahepatic HBV eee DNA (Yokosuka et al, 1985;.…”
Section: Hepadnaviral Supercoiled Dnamentioning
confidence: 99%
“…It was further shown that D-FIAU is a more efficient substrate for mitochondrial thymidine kinase 2 than for cytosolic thymidine kinase 1 [65], and that D-FIAU-triphosphate inhibited mitochondrial function through its incorporation into mitochondrial DNA by DNA polymerase-Á, leading to ultrastructural defects of mitochondria and accumulation of intracytoplasmic lipid droplets [52,66]. D-FMAU was found to inhibit viral replication very efficiently in both the woodchuck and the duck models [57,67,68]. In WHVinfected woodchucks, the antiviral effect was sustained after cessation of therapy, but was associated with severe toxicity [67].…”
Section: Pyrimidine Analogsmentioning
confidence: 99%